Radon in groundwater sources of Bosso Community in North Central Nigeria and concomitant doses to the public - Kolo, Matthew Tikpangi; Khandaker, Mayeen Uddin *; Isinkaye, Matthew O.; Ugwuanyi, Anayo; Chibueze, Nwachukwu; Falade, Opeyemi; Onuche, Paul; Alqahtani, Amal; Bradley, D.A. *; Ashraf, I.M. (Elsevier, 2023)
Realizing the probable health hazards from radon exposure, potable groundwater samples (hand-dug wells and boreholes) in the Bosso community of North Central Nigeria were collected and assayed for radon concentration. Durridge RAD-7 detector together with RAD-H2O accessories was employed in this study. The committed effective dose to different ICRP age groups was computed using various parameters including the annual water consumption characteristics. The mean 222Rn activity in water samples from hand-dug wells and boreholes were 9.81 ± 1.85 Bq/L and 24.78 ± 2.48 Bq/L respectively. The average whole-body committed effective dose due to ingestion and inhalation of waterborne radon from the two groundwater sources are 0.026 mSv/y and 0.067 mSv/y for hand-dug wells and boreholes respectively, which are below the safety threshold of 0.1 mSv/y recommended by the European Union. The results showed that there is no significant radiation threat to public health from inhalation and ingestion of waterborne radon within the community.